Enhanced Degradation of Phenol in Aqueous Solution via Persulfate Activation by Sulfur-Doped Biochar: Insights into Catalytic Mechanisms and Structural Properties - Guanyu Wang; Lihong Kou; Chenghao Li; Bing Xu; Yuanfeng Wu (Nanomaterials, 2025)
In this study, sulfur-doped biochar (SBC) was successfully synthesized using peanut shells as the raw material and sulfur powder as the sulfur source. The composition, structural characteristics, and catalytic performance of SBC in the degradation of phenol via persulfate (PDS) activation were systematically investigated. Characterization results demonstrate that the prepared SBC exhibited a typical lamellar structure with abundant pores and fissures on its surface. XPS analysis confirmed the successful incorporation of sulfur into the biochar matrix, primarily in the form of thiophene. Under the optimized condition of a 20% sulfur doping ratio, the SBC exhibited high efficiency in activating PDS, achieving a phenol degradation rate of 97%. Remarkably, the removal rate remained at 81% even after the fifth cycle, indicating excellent cyclic stability. Density functional theory (DFT) calculations and electrochemical impedance spectroscopy (EIS) measurements further revealed that sulfur doping significantly modified the electron density distribution of the biochar, reducing its surface electrochemical impedance from 32.88 Ω to 13.64 Ω. This reduction facilitated efficient electron transfer during the catalytic process. This study provides both experimental and theoretical insights into the charge distribution characteristics of sulfur-doped biochar, offering valuable references for understanding the mechanism of PDS activation by SBC.